Factores externos e internos determinantes de la orientación de la cultura estratégica de las empresas - J. Febles Acosta; J. R. Oreja Rodríguez (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2008)
The purpose of the research has been to empirically verify the influence of aspects related to the internal scope of the company (property and size of the company) and the environment (activity sector) in its strategic culture. The results of the factorial analysis first revealed the predominance of four types of corporate culture in the analyzed companies, labeled as: 'Adaptation', 'Participation', 'Commitment' and 'Formation'. The statistical contrast of the formulated hypotheses confirmed that internal and external factors determine the strategic culture. The statistical approach also revealed other relations non-hypothesi previously, that are susceptible of validation in future investigations.
Keywords: 330; strategic culture; size; property; sector; factor analysis